Checklists for vocabulary study - Yorkey, Richard (New York Longman Group United Kingdom, 1981)
Students who find that they often cannot express themselves because they are at a loss for the right word will find practical help in Checklists for Vocabulary Study. The 16 checklists are organized around patterns of morphological change. For example, verbs to which "-ment" is added to form a noun are included in a single checklist. Thus, students learn not only accomplish, achieve, and reinforce, but also accomplishment, achievement, and reinforcement. Verb, noun, adjective, and adverb forms are all listed when applicable, thus giving the students the full range of use of each word. Using the checklists, the students learn the patterns of part-of-speech change as they learn meanings. Ample practice material, focusing on both meaning and form, follows each checklist, and review tests allow students to evaluate their progress and identify those words that they need to review. Checklists for Vocabulary Study is ideal for self-study or work in groups. Since students study only those words whose meanings they are unsure of, the text is responsive to highly individualized needs.